Strategi Penggunaan Bahasa Baku dalam Meningkatkan Kemampuan Berbahasa Anak - Fauzan, Alfi Nura; Sembiring, Claudia Cresensia; Febriana, Ika; Nababan, Lindawati Elisabeth; Mawarni, Rina; Tambun, Tia Rosanna; Zahiroh, Zalfa (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to examine strategies for using standardized language in improving children's language skills. Standardized language is an important foundation in establishing the basis of good language skills and ensuring children have a strong foundation for effective communication. The research method used in this study is a qualitative literature study by analyzing various relevant sources such as scientific journals, research reports, textbooks, and other secondary data sources. The results of the study show that in general there are still many children who still do not fully understand the difference between standard and non-standard language. Children still rely on the language they hear and use daily. This research emphasizes the role of teachers and parents is very important in improving standard Indonesian language for children. Some of the strategies described in this study to help children improve standardized language such as inviting children to talk with interesting topics and by telling stories.